PERBEDAAN EFEKTIFITAS PENDIDIKAN KESEHATAN MELALUI MEDIA VIDEO ANIMASI DAN POWER POINT TERHADAP PENGETAHUAN REMAJA PUTRI DALAM MENGHADAPI MENARCHE (JURNAL KESEHATAN MERCUSUAR, 2021)
On 2017 Indonesian Youth Demographic and Health Survey (IDHS) report stated that 12.3% of young women still do not know about menstruation as a sign of physical changes during puberty. Lack of information and knowledge related to menstruation can affect the perception and readiness of young women in facing menarche. There needs to be an effort to increase adolescent knowledge about menarche through the provision of health education with appropriate methods and media. The purpose of this study was to determine the differences in the effectiveness of health education through animated video media and power point on the knowledge of young women in dealing with menarche. This type of research is a quasi-experimental research (quasi-experimental design) with a nonequivalent control group design. The study was conducted on June 19, 2021. The population in this study were all students of 13 elementary school Kapalo Koto class V and VI, totaling 48 people with a sample of 32 people obtained using the Federer formula. The sampling technique is purposive sampling. The instrument used is a questionnaire. Analysis test using Paired Sample T-Test and Independent Sample T-Test. Based on the results of the study, the average knowledge before being given health education through animated video was 13,62 and after being given health education it increased to 20,19. Meanwhile, the media power point is 13,31 increasing to 17.31. There was a significant difference in the knowledge of adolescent girls before and after being given health education through animated video media and power point=0,000 (p
Keywords: Pendidikan Kesehatan; Video Animasi; Power Point; Menarche; Health Education; Animated Video; Power Point; Menarche